Надо выражение 3n² -n (4n-6m) 5a+2a(3a+5) a(a+b)-b(a-b) 2x(x-y)-y(y--2x) 2p(1 -p-3p²)-3p(2-p-2p²) 2c (5a-3c² )-c(a-6c²)+3a(9a-c) раскройте скобки с(2а+b )

1234567890love 1234567890love    1   08.07.2019 17:30    0

Ответы
yaps61 yaps61  16.09.2020 18:17
3n²-n(4n-6m) = 3n²-4n²+6mn = -n²+6mn

5a+2a(3a+5) = 5a+6a²+10a = 15a+6a²

a(a+b)-b(a-b) = a²+ab-ab+b² = a²+b²

2x(x-y)-y(y-2x) = 2x²-2xy-y²+2xy = 2x²-y²

2p(1-p-3p²)-3p(2-p-2p²) = 2p-2p²-6p³-6p+3p²+6p² = -4p+p²-3p³

2c(5a-3c²)-c(a-6c²)+3a(9a-c) = 10ac-6c³-ac+6c³+27a²-3ac = 6ac+27a²

с(2а+b) = 2ac+ab
ПОКАЗАТЬ ОТВЕТЫ
kirill031312 kirill031312  16.09.2020 18:17
3n²-n(4n-6m) = 3n²-4n²+6mn = -1n²+6mn; 5a+2a(3a+5) = 5a+6a²+10a = 15a+6a²; a(a+b)-b(a-b) = a²+ab-ab+b² = a²+b²; 2x(x-y)-y(y-2x) = 2x²-2xy-y²+2xy = 2x²-y²; 2p(1-p-3p²)-3p(2-p-2p²) = 2p-2p²-6p³-6p+3p²+6p² = -4p+p²-3p³; 2c(5a-3c²)-c(a-6c²)+3a(9a-c) = 10ac-6c³-ac+6c³+27a²-3ac = 6ac+27a²; с(2а+b) = 2ac+cb.
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика